The Optimal Income Taxation of Couples - Kleven, Henrik; Kreiner, Claus Thustrup; Saez, Emmanuel (Econometrica, 2009)
This paper analyzes the general nonlinear optimal income tax for couples, a multidimensional screening problem. Each couple consists of a primary earner who always participates in the labor market, but makes an hours-of-work choice, and a secondary earner who chooses whether or not to work. If second-earner participation is a signal of the couple being better (worse) off, we prove that optimal tax schemes display a positive tax (subsidy) on secondary earnings and that the tax (subsidy) on secondary earnings decreases with primary earnings and converges to zero asymptotically. We present calibrated microsimulations for the United Kingdom showing that decreasing tax rates on secondary earnings is quantitatively significant and consistent with actual income tax and transfer programs.